The impact of timing of antimicrobial therapy on outcome and mortality in severe sepsis and septic shock - Zahra, Ahmed Najah A (International journal of health sciences, 2024)
Even though new antimicrobial treatments have been available for over 60 years, the fatality rate from septic shock has not decreased. Evolutionary pressure on microbial pathogens has, as expected, led to selection towards resistant species as a consequence of the creation of ever more broad-spectrum and strong antimicrobials. The ineffectiveness of antibiotic treatment of septic shock un the decades that followed may have been a result of this phenomena. The treatment of septic shock has traditionally focused on resuscitative measures. The management of these serious illnesses has not prioritised the prompt provision of effective antibiotic treatment.